Does intelligent manufacturing promote a breakthrough in green innovation? Evidence from China - Dong, Xiangshu; Du, Yongjiao; Zhao, Mengchao; Xiao, Xiang (Frontiers in Environmental Science, 2025)
Breakthroughs in green innovation (BGI) have become increasingly prominent in spearheading green technology, while intelligent manufacturing (IM) offers a fresh technical paradigm for the manufacturing industry’ green development. Yet, due to the limitations in measuring BGI, existing research on IM and BGI has been ignored. By devising a ground-breaking approach to BGI, this paper takes the IM pilot demonstration projects as an ideal quasi-natural experiment and investigates the influence of IM on BGI. Our findings indicate that IM can effectively enhance BGI which are further validated by a series of rigorous examinations. Further mechanism analysis reveals that crowding-in R&D resources, strengthening green open innovation, and alleviating agency conflict play potential pathways in bridging the nexus between IM and BGI. A heterogeneity analysis highlights that IM has the potential to disrupt the technological path dependency observed in high-pollution and high-energy consumption industries. Further research suggests that IM can form a joint effect with environmental regulations to promote BGI. BGI driven by IM can also improve both the firm’s economic and environmental, social, and governance (ESG) performance, leading to a “win-win” scenario for economic performance and green development. Our study confirms that promoting IM in emerging countries is indispensable for enhancing BGI, which serves as the new impetus for green development.